TRPV4 channel activation induces the transition of venous and arterial endothelial cells toward a pro‐inflammatory phenotype. Issue 3 (29th January 2021) - Beddek, Kathia; Raffin, Florent; Borgel, Delphine; Saller, François; Riccobono, Diane; Bobe, Régis; Boittin, François‐Xavier
Abstract: The Transient Receptor Potential Vanilloid 4 (TRPV4) of endothelial cells contributes to many important functions including the regulation of Ca 2+ homeostasis, cell volume, endothelial barrier permeability, and smooth muscle tone. However, its role in the transition of endothelial cells toward a pro‐inflammatory phenotype has not been studied so far. Using both arterial and venous endothelial cells, we first show that the pharmacological activation of TRPV4 channels with GSK1016790A, a potent TRPV4 agonist, triggers robust and sustained Ca 2+ increases, which are blocked by both TRPV4 antagonists HC067047 and RN9893. TRPV4 activation also triggers the actin cytoskeleton and adherens junction (VE‐Cadherin) rearrangement in both arterial and venous endothelial cells and leads to rapid decreases of trans‐endothelial electrical resistance. In addition to its effect on endothelial barrier integrity, TRPV4 activation selectively increases ICAM‐1 surface expression in arterial and venous endothelial cells, due to the stimulation of ICAM‐1 gene expression through the NF‐κB transcription factor. TRPV4 channel activation also induced apoptosis of venous and arterial endothelial cells, while TRPV4 blockade reduced apoptosis, even in the absence of TRPV4 activation. As altered barrier integrity, increased adhesion molecule expression and apoptosis are hallmarks of the pro‐inflammatory state of endothelial cells, our results indicate that TRPV4 channel activity can induce the transition of both venous and arterial endothelial cells toward a pro‐inflammatory phenotype. Abstract : Using both arterial and venous endothelial cells, this paper shows that TRPV4 channel activity can induce the transition of both venous and arterial endothelial cells toward a pro‐inflammatory phenotype, as evidenced by altered barrier integrity, increased adhesion molecule expression, and apoptosis.